Greenhouse evaluation of maize performance and changes in chemical properties of soil following application of winery solid waste composts - Masowa, Manare Maxson (University of Limpopo, 2015)
Winery solid waste materials namely, wine filter materials (FM), grape marc (berry stalks, skins and seeds) and chopped grapevine pruning canes were composted in heaps through a thermophilic process. The filter materials were mixed with the grape marc and grapevine prunings at five rates (10%, 25%, 50%, 75% and 100%) to produce five composts herein designated as C10FM, C25FM, C50FM, C75FM and C100FM, respectively. A laboratory incubation study was thereafter carried out to determine the nutrient release potential of the composts using two soil types with varying textural characteristics. Each compost was mixed with soil at a rate equivalent to 200 kg N ha-1 and the mineral N, available P and exchangeable K content determined over 42 days incubation period. Results revealed that the composts possess high C content and low C:N ratios; and released significantly higher NH4-N and K concentration relative to un-amended control. The differences in the amount of P mineralised among the five compost treatments were not significant while significantly higher amount of K was mineralised at higher FM mix rates. The composts were applied to maize cv. SNK2147 on sandy soil in a greenhouse pot study at five rates (5, 10, 20, 40 and 80 t ha-1) to determine their effects on crop growth and yield as well as on selected soil chemical properties. An un-fertilised control and NPK fertiliser treatments were included for comparison. The pots were arranged in a completely randomized design, with each treatment replicated four times. The C50FM, C75FM and C100FM treatments applied at 80 t ha-1 gave significantly higher maize dry matter yield than the NPK fertiliser treatment. Quantitative estimates of the optimum compost rate for dry matter production ranged from 450 to 1842 g pot-1. Application of these composts significantly increased dry matter yield, plant height, stem diameter and the number of functional leaves per plant compared to the un-fertilised control. The K content of shoot from composts treatments exceeded the critical nutritional level of 3.3%. Plant tissue Zn content from C10FM, C25FM and C50FM treatments exceeded the critical nutritional level of 15 mg kg-1 while the residual soil K, Na and Zn contents after crop harvest were significantly increased following compost application. Similarly, the residual P was significantly increased in C25FM, C75FM and C100FM treatments after harvest. In conclusion, application of these composts exerted beneficial effects on maize performance and soil. Field studies under variable conditions are recommended to validate these findings. Keywords: wine, compost, nutrient release potential, maize, soil chemical properties
Thesis (M.Sc.(Soil Science)) -- University of Limpopo, 2015
Keywords: Wine; Compost; Nutrient release potential; Soil chemical properties; Maize; Greenhouse management; Greenhouse plants